The euro area crisis: a short history - Jacques Delors Institut; Haas, Jörg; Gnath, Katharina (Gütersloh, 2016)
"In this policy paper, Jörg Haas and Katharina Gnath argue that the most widely shared explanations of the crisis have an important element in common: they point to the importance of debt imbalances in the euro area."